Multi‐year net ecosystem carbon balance of a restored peatland reveals a return to carbon sink. (9th October 2018) - Nugent, Kelly A.; Strachan, Ian B.; Strack, Maria; Roulet, Nigel T.; Rochefort, Line
Abstract: Peatlands after drainage and extraction are large sources of carbon (C) to the atmosphere. Restoration, through re‐wetting and revegetation, aims to return the C sink function by re‐establishing conditions similar to that of an undrained peatland. However, the time needed to re‐establish C sequestration is not well constrained due to the lack of multi‐year measurements. We measured over 3 years the net ecosystem exchange of CO2 (NEE), methane ( F CH 4 ), and dissolved organic carbon (DOC) at a restored post‐extraction peatland (RES) in southeast Canada (restored 14 years prior to the start of the study) and compared our observations to the C balance of an intact reference peatland (REF) that has a long‐term continuous flux record and is in the same climate zone. Small but significant differences in winter respiration driven by temperature were mainly responsible for differences in cumulative NEE between years. Low growing season inter‐annual variability was linked to constancy of the initial spring water table position, controlled by the blocked drainage ditches and the presence of water storage structures (bunds and pools). Half‐hour F CH 4 at RES was small except when Typha latifolia ‐invaded drainage ditches were in the tower footprint; this effect at the ecosystem level was small as ditches represent a minor fraction of RES. The restored peatland was an annual sink for CO2 (−90 ± 18 g C m −2 year −1 ), a source of CH4 (4.4 ± 0.2 g C m −2 year −1 ), and a source of DOC (6.9 ± 2.2 g C m −2 year −1 ), resulting in mean net ecosystem uptake of 78 ± 17 g C m −2 year −1 . Annual NEE at RES was most similar to wetter, more productive years at REF. Integrating structures to increase water retention, alongside re‐establishing key species, have been effective at re‐establishing the net C sink rate to that of an intact peatland. Abstract : We measured over 3 years the net ecosystem exchange of CO2, methane, and dissolved organic carbon (DOC) at a restored post‐extraction peatland and compared our observations to the C balance of an intact reference peatland that has a long‐term continuous flux record. The restored peatland was an annual sink for CO2, and a source of methane and DOC, resulting in a mean annual net ecosystem uptake of C. Integrating structures to increase water retention, alongside re‐establishing key species, have been effective at re‐establishing the net C sink rate to that of an intact peatland.